2021
DOI: 10.1038/s41598-021-04242-3
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of temperature on the transmissibility and virulence of COVID-19 in Tokyo, Japan

Abstract: Assessing the impact of temperature on COVID-19 epidemiology is critical for implementing non-pharmaceutical interventions. However, few studies have accounted for the nature of contagious diseases, i.e., their dependent happenings. We aimed to quantify the impact of temperature on the transmissibility and virulence of COVID-19 in Tokyo, Japan, employing two epidemiological measurements of transmissibility and severity: the effective reproduction number ($$R_{t}$$ R … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…Another significant study in the USA investigated the attributable fractions of the mean ambient temperature at 3.7% [ 44 ]. Similarly, a study in Tokyo also reported a cumulative RR of 1.3 (95% CI: 1.1–1.7) at the first mean ambient temperature percentile (i.e., 3.3 °C), which provides empirical support for our findings [ 48 ]. Furthermore, the laboratory studies conducted by Chin et al suggested that SARS-CoV-2 is stable at approximately 4.0 °C, but at approximately 70.0 °C (higher temperature), the virus inactivation time decreases to five minutes, supporting existing epidemiological findings [ 68 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Another significant study in the USA investigated the attributable fractions of the mean ambient temperature at 3.7% [ 44 ]. Similarly, a study in Tokyo also reported a cumulative RR of 1.3 (95% CI: 1.1–1.7) at the first mean ambient temperature percentile (i.e., 3.3 °C), which provides empirical support for our findings [ 48 ]. Furthermore, the laboratory studies conducted by Chin et al suggested that SARS-CoV-2 is stable at approximately 4.0 °C, but at approximately 70.0 °C (higher temperature), the virus inactivation time decreases to five minutes, supporting existing epidemiological findings [ 68 ].…”
Section: Discussionsupporting
confidence: 84%
“…Time-series statistical regression modeling, which is often used to quantify short-term associations of environmental exposures with health outcomes, such as infectious diseases, would allow investigators to control for seasonality, long-term trends, other confounders, and autocorrelation, as well as explore the association of delayed exposure effects [ 46 ]. Despite the advantages of this method, its use has not been overly prevalent in research [ 13 , 44 , 45 , 47 , 48 ]. Additionally, many of these previous studies did not control for or only controlled for a few crucial potential confounders when describing the disease transmission dynamics, which include other behavioral and environmental drivers, the implementation of non-pharmaceutical interventions (NPIs), and temporal changes in population immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenicity of rhabdoviruses is usually influenced by temperature, host species, and age [31,32]. Boovo et al [28] demonstrated that high mortality in Carpio fry exposed to CAPRV at 10 or 15°C.…”
Section: Discussionmentioning
confidence: 99%
“…On reporting the results, we expressed the effects of meteorological variables relative to a reference level set to be the median of observation distribution. We obtained associations curves representing how the relative risk change by different levels of the meteorological variables, which can be compared with the results of previous studies ( Guo et al, 2021 ; Nottmeyer and Sera, 2021 ; Yamasaki et al, 2021 ; Zhu et al, 2021 ). This representation understates uncertainty in the reference level and overstates uncertainty in other exposure levels.…”
Section: Discussionmentioning
confidence: 99%